Pengaruh Integrasi Teknologi Blockchain dan Struktur Organisasi terhadap Efisiensi Audit Akuntansi pada Perusahaan XYZ di Indonesia - Rijal, Syamsu; Devi, Erwina Kartika; Saputra, Ahmad Edi; Fatimah, Siti; Sarwono, Sarwono (Eastasouth Institute, 2024)
This research explores the impact of the integration of Blockchain technology and organizational structure on the efficiency of accounting audits at XYZ Company in Indonesia through quantitative analysis. Surveys, interviews and document analysis were conducted to collect data from employees involved in the accounting and audit process. The results show a moderate level of integration of Blockchain technology and organizational decentralization, with a positive correlation between these factors and audit efficiency. Regression analysis confirms the predictive power of Blockchain integration and organizational structure on audit efficiency. These findings highlight the importance of technological and organizational factors in shaping audit outcomes, with implications for theory and practice in the accounting profession.